Synthesis and characterization of different transiton metal-alginate based heterogeneous catalyst for esterification reaction. - Pua Fei Ling @ Grace Pua (2017)
Volume :709, Issue No :-, Article ID :-, Page Start :57, Page End :60, ISSN :1662-9795